2019
DOI: 10.18203/2349-3291.ijcp20193702
|View full text |Cite
|
Sign up to set email alerts
|

Kramer’s scale or transcutaneous bilirubinometry: the ideal choice of a pediatrician? can we trust our eyes?

Abstract: Background: Neonatal hyperbilirubinemia, though benign in 80% cases, can lead to kernicterus if not diagnosed and treated early. The golden method of estimation is measuring serum bilirubin levels. Both Kramer’s scale and Transcutaneous bilirubinometer are non -invasive methods. Its high time the pediatricians choose an ideal non-invasive and reliable method to detect hyperbilirubinemia. Objective of this study is to find out which has a better correlation with serum bilirubin - transcutaneous bilirubinometer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…We found a strong correlation between TCB and TSB in accordance with previous studies [10]. Two recent studies from Indonesia and India, respectively, reported higher correlations between TCB and TSB in (late) preterm infants [17,19]. TCB overestimated TSB with 26 µmol/L at 24 h and 21 µmol/L at 48 h [19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found a strong correlation between TCB and TSB in accordance with previous studies [10]. Two recent studies from Indonesia and India, respectively, reported higher correlations between TCB and TSB in (late) preterm infants [17,19]. TCB overestimated TSB with 26 µmol/L at 24 h and 21 µmol/L at 48 h [19].…”
Section: Discussionsupporting
confidence: 91%
“…Two recent studies from Indonesia and India, respectively, reported higher correlations between TCB and TSB in (late) preterm infants [17,19]. TCB overestimated TSB with 26 µmol/L at 24 h and 21 µmol/L at 48 h [19]. Greco et al [16] reported that TCB measured before or during PT with the JM-103 overestimated TSB with an MD of 5 (±50) µmol/L and corresponding LoA from −92 to 103 µmol/L.…”
Section: Discussionmentioning
confidence: 96%
“…In Varughese study, the males were 54.4% while female babies were 45.6%. Out of 450 babies, 65.1% babies were delivered by vaginal delivery, 5.1% by instrumental delivery and 29.8% were delivered by Caesarean section [16].…”
Section: Discussionmentioning
confidence: 99%
“…Second, there are considerable difficulties in establishing gestational age [31,32] and time of birth of neonates admitted to hospitals serving rural areas in sub-Saharan Africa, where most deliveries occur at home, and neonates are admitted after the onset of NNJ in the community. Moreover, there is considerable debate about the criteria for a safe level of bilirubin in sick neonates [33][34][35].…”
Section: Participantsmentioning
confidence: 99%